Energy efficient spray drying by increased feed dry matter content: investigations on the applicability of Air-Core-Liquid-Ring atomization on pilot scale. Issue 10 (1st July 2020) - Wittner, Marc O.; Karbstein, Heike P.; Gaukel, Volker
Abstract: Spray drying is the main process for production of powdered products from liquid sources. One way to reduce energy consumption of spray drying processes is preconcentration of feed liquids by using more energy efficient techniques, such as membrane reactors or falling film evaporators. As feed viscosity increases with dry matter content, efficient atomization at high viscosities is necessary. In contrast to standard pressure swirl (PS) atomizers, Air-Core-Liquid-Ring atomization may be an option. Experiments on a pilot scale show its high potential for application in spray drying processes as feed dry matter content may be increased up to 50% compared to PS atomization. The theoretical energy savings associated with the 50% feed solids increment is about 29%. Further investigations are required to assess the complexity, the practicality and the potential benefits for industrial-scale operations.